Modeling User Interactions for Complex Visual Search Tasks. - Chang, Remco.; Zhao, Helen.; Lin, Quan.; Ottley, Alvitta. (Tufts University. Tisch Library., 2017)
Modeling a user's interactions is intimately tied to many areas of research in the fields of HCI and Visual Analytics. Most notably, developing adaptive visual interfaces and effectively prefetching for large datasets, first requires understanding the user's behavior and analytical process. In this work, we demonstrate the potential of using a user's mouse movements and clicks to achieve this goal. In an online study, we gather users' interactions as they perform a complex visual search task. Our results indicate a significant difference between the search strategies employed by users who were quick at completing the task and those who were slow.